2017
DOI: 10.1177/1479164117710392
|View full text |Cite
|
Sign up to set email alerts
|

Circulating annexin A5 levels are associated with carotid intima-media thickness but not coronary plaque composition

Abstract: Background: Annexin A5 (anxA5) is involved in processes which are crucial in atherogenesis. However, anxA5's relationship with atherosclerotic lesion extension and plaque composition in high-risk patients with type 2 diabetes remains unclear. Thus, we characterized the association between circulating anxA5 levels with atherosclerotic burden and coronary plaque composition in diabetes mellitus patients. Methods: Intima-media thickness was determined in 96 diabetes mellitus patients with stable coronary artery d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
2
2
0
Order By: Relevance
“…The relationship of endogenous ANXA5 with atherosclerotic complications is not well defined. While the levels of circulating ANXA5 have been shown to be associated with the severity of coronary stenosis [ 46 ] and subclinical atherosclerosis outcomes in patients with T2DM or systemic lupus erythematosus [ 33 , 47 ], another study revealed no direct association between ANXA5 levels and CIMT progression [ 30 ], consistent with the present study. The differences between all the above reported studies could be related to study design, population sample size, and/or the nature and progression of disease among patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The relationship of endogenous ANXA5 with atherosclerotic complications is not well defined. While the levels of circulating ANXA5 have been shown to be associated with the severity of coronary stenosis [ 46 ] and subclinical atherosclerosis outcomes in patients with T2DM or systemic lupus erythematosus [ 33 , 47 ], another study revealed no direct association between ANXA5 levels and CIMT progression [ 30 ], consistent with the present study. The differences between all the above reported studies could be related to study design, population sample size, and/or the nature and progression of disease among patients.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that levels of circulating sF11R were notably higher than previously reported values for hemodialysis, hypertensive, and patients with normal or nonobstructive disease, suggesting a role of sF11R in the pathophysiology of diabetes [ 18 , 19 , 29 ]. While, several studies reported abnormal elevations of circulating ANXA5 in familial hypercholesterolemia, hypertensive patients, and patients with myocardial infarction [ 30 , 31 , 32 ], levels of ANXA5 among the patients of current study were within normal range (0–2 ng/mL), similar to those reported in healthy population [ 24 , 33 ]. Interestingly, we found that sF11R levels correlated positively with ANXA5 levels.…”
Section: Discussionsupporting
confidence: 83%
“…Endogenous annexin A5 in all treatment groups was similar to the normal basal circulating plasma levels of healthy volunteers (Matsuda et al, 2003;Van Heerde et al, 2003;Burgmaier et al, 2017). Plasma SY-005 concentrations were obtained by subtracting endogenous levels from total annexin A5 concentrations.…”
Section: Discussionmentioning
confidence: 74%
“…However, the role of ANXA5 in CAD remains controversial. Burgmaier et al revealed that in high-risk diabetic patients, the level of circulating ANXA5 correlated with the thickness of the carotid intima, but not with the composition of the coronary plaque ( Burgmaier et al, 2017 ). And Hashemi et al reported that the frequency of polymorphism in ANXA5 gene was not relevant to the presence of in-stent restenosis ( Hashemi et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%